2019
DOI: 10.3390/ijerph16132379
|View full text |Cite
|
Sign up to set email alerts
|

Coworking Spaces: The Better Home Office? A Psychosocial and Health-Related Perspective on an Emerging Work Environment

Abstract: With the ongoing flexibilization of work, new trends concerning work outside the company’s premises such as coworking spaces are on the rise. Coworking spaces are designed to offer collaboration and community in furnished and equipped workspaces on a rental base. There is a growing body of scientific literature on coworking spaces with empirical results of qualitative and quantitative research. The present study adds to the latter by examining psychosocial demands experienced by coworkers in Germany based on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 43 publications
1
56
0
5
Order By: Relevance
“…Amongst the various criteria developed, the concept of satisfaction has become the most widely used in evaluating work environments. It has been used to assess the performance of all types of work environments (Hill et al , 2003; Robelski et al , 2019) as it indicates the general levels of success, measures the users’ experience, points out the irksome aspect of work environments and predicts users’ responses to future work environments.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Amongst the various criteria developed, the concept of satisfaction has become the most widely used in evaluating work environments. It has been used to assess the performance of all types of work environments (Hill et al , 2003; Robelski et al , 2019) as it indicates the general levels of success, measures the users’ experience, points out the irksome aspect of work environments and predicts users’ responses to future work environments.…”
Section: Literature Reviewmentioning
confidence: 99%
“…45 % der Coworker zuvor im Homeoffice gearbeitet haben [11]. Darüber hinaus arbeiten 82 % der Coworker weiterhin zumindest teilweise von zuhause aus [4], wobei vor allem die soziale Interaktion von vielen Coworkern im Vergleich zum Homeoffice wertgeschätzt wird [24]. Zudem gilt Netzwerkarbeit als wesentliches Motiv für das Arbeiten in Coworking Spaces [8,12,18,23].…”
Section: Der Durchschnittliche Coworkingunclassified
“…In terms of initial engagements, studies have shown, for example, how, under corporate planning, healthcare organizations purposefully attract and retain workers and clients by instilling particular affective atmospheres of competent, timely, energetic and passionate care (Ducey, 2007; Martin et al., 2019; Solomon, 2011). Other studies meanwhile have considered the atmospheres of well‐being, collaboration, community and creativity that emerge in novel working scenarios and spaces, such as with ‘coworking’ (Robelski et al., 2019; Waters‐Lynch & Duff, 2019).…”
Section: Future Inquiries: Health In the New Capitalismmentioning
confidence: 99%